Trends in Palm Oil Supply Chain and Trade: A Bibliometric Approach - Judijanto, Loso (Westscience Press, 2025)
This study explores the global research landscape on palm oil supply chains and trade through a bibliometric analysis using data exclusively sourced from the Scopus database and visualized via VOSviewer. The analysis spans publications from 2000 to 2024, identifying patterns in authorship, institutional affiliations, country collaborations, keyword co-occurrence, and thematic evolution. Results indicate a sharp increase in scholarly output beginning in 2015, with Indonesia and Malaysia emerging as the most prolific contributors. The research themes have shifted from early focuses on bioenergy and environmental emissions to more recent concerns such as deforestation, certification, governance, and sustainability. Co-authorship networks reveal disciplinary fragmentation between environmental and technical research communities, while international collaboration is strongest between Southeast Asian producers and Western academic institutions. The study highlights the need for more interdisciplinary integration and identifies emerging research gaps related to commerce, biodiversity, and land-use change. These findings offer strategic insight for researchers, practitioners, and policymakers seeking to navigate and contribute to the evolving discourse on sustainable palm oil supply chains.